Kierunki rozwoju małej i średniej przedsiębiorczości w powiecie przemyskim - Radochońska-Wasiewicz, Elżbieta (Development directions for small and medium-sized enterprises in the county of Przemysl, 2006)
The article describes the tourist attractions of the county of Przemyśl which are considered to be an opportunity for the development of small and medium-sized enterprises. The research results presented show both the structure of businesses in the county and their opinion about the town’s tourist attractions and possible ways of using their advantages.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 259-268